Effect of open innovation on firm performance through type of innovation: Evidence from SMES in Malang City, East Java, Indonesia - Edy Yulianto; Supriono (Cogent Business & Management, 2023)
This study investigates the effect of open innovation on firm performance through different types of innovation, namely, product, service, and process innovation. Set in the context of the small and medium enterprise (SME) sector, the study examines SME capabilities obtained from outbound and inbound knowledge flow to adopt innovation. Several studies have demonstrated that the open innovation variable and the type of innovation are some of the most important factors influencing firm performance. This study uses quantitative methods and a research sample of 107 SMEs in Malang City, East Java Province, Indonesia. The results indicate that open innovation has a positive and significant effect on product, process, and service innovation, but does not have a significant direct effect on firm performance. In addition, product innovation and process innovation do not have a significant effect on firm performance; however, service innovation does have a significant effect on firm performance. Furthermore, service innovation is able to mediate the relationship between open innovation and firm performance. The study results and their theoretical and practical implications are also discussed.
Keywords: 650; firm performance; open innovation; process innovation; product innovation; service innovation